158-LB: Effect of Vitamin D Replacement on Glycemic Status and Pregnancy Outcomes in Vitamin D–Deficient Subjects with Gestational Diabetes Mellitus - BAIDYA, ARJUN; PATHAK, YASHASWI; SENGUPTA, NILANJAN; KUMAR SAHANA, PRANAB; GOSWAMI, SOUMIK; TARENIA, SILIMA; BANERJEE, ABHIRUP; CHATTOPADHAYAY, MOUNAM; HATHI, DEEP; GAIKWAD, PRASHANT MANOHAR; DAS, NILADRI (Diabetes (New York, N.Y.), 2022)
Aims: To study the effect of Vitamin D replacement on glycaemic control and pregnancy outcomes in Gestational Diabetes Mellitus patient with Vitamin D deficiency. Methods: In this prospective, open-label interventional study 60 GDM subjects with Vitamin D deficiency were divided into 2 groups of 30 each, and the intervention group received 60,000 IU of cholecalciferol weekly for 6 weeks and then monthly for the duration of pregnancy. while the control group did not. Vitamin D status was re-assessed at 32 weeks of gestation for both groups. The glycaemic status was assessed using fasting plasma glucose and 1-hour and 2-hour postprandial glucose at 30 weeks of gestation and at time of delivery. Feto-maternal outcomes: Time of delivery (weeks of gestation) , method of delivery, pre-eclampsia, still-birth, neonatal hypoglycaemia, neonatal jaundice, birth weight, head circumference of the baby, APGAR score at 5 minutes in both groups were also assessed. Results: In the intervention group 87% (26 out of 30) of subjects had become vitamin D sufficient. None of the subjects in the control group had become vitamin D sufficient. Fasting Plasma Glucose was significantly lower in the intervention group as compared to the control group) at 30 weeks of gestation (99.57±18.12 vs. 107.90±17.53 mg/dl; p=0.039) and at time of delivery (98.53±15.41 vs. 104.47±18.71mg/dl; p=0.044) . Both 1 hour and 2-hour postprandial plasma glucose (136.81±20.29 vs. 152.58±16.76; p=0.004 and 118±22.10 vs. 132.64±18.48 mg/dl; p=0.017 respectively) values were also significantly lower in the intervention group at the time of delivery. Birth weight was significantly lower in the control group as compared to the intervention group (2348.13±388.965 vs. 2778.67±270.288 gm; p=0.034) . All other neonatal parameters were similar in the two groups. Two subjects in the control group had still-births. Conclusion: Correction of Vitamin D deficiency in GDM subjects may result in better control of their plasma glucose levels. Low Vitamin D levels in GDM subjects may be associated with lower birth weight.